ON THE ENFORCEABILITY LEGAL RESPONSIBILITY CRIMINAL STATE (EUROPEAN AND ASIAN LAW REVIEW, 2024)
The phenomenon of realization of legal responsibility of the state, which has gone beyond the framework of generally accepted public-law relations, is considered. The situation arising in this case requires the restoration of the rights of society and the individual in a country where power is usurped by a criminal regime, as well as international law violated by a criminal state. The legal consequences for the delinquent State in case of its disregard for the norms of international and national law are analyzed.
Keywords: legal responsibility, international legal responsibility, criminal legal responsibility, constitutional legal responsibility, customary legal responsibility, criminal State, delinquent State, extraterritorial jurisdiction, peace enforcement, post-conflict resolution